Simulation Testing On Improved Design Of College Chair Using Finite Element Method (Fem) - Puspita Kartika Wilis; Lee Hyunsoo (eProceedings of Engineering, 2018)
Abstract In the university life, study activity is a main part of the learning that aims to make students get more knowledge in the focused area of studentsâ€™ interest. College chair is one kind of furniture that is designed for university student and in this research college chair that will be researched is improved from the existing college chair. In the product development process phase, there are testing and refinement stage. This stage is done after the product design have been generated. The sample also needed to facilitate the work and referred as prototype. Prototype is product approximation along one or more dimensions of interest. In a study entitled â€œImplementation of Quality Function Deployment Method in Design Improvement for College Chairâ€, the design has been done considering the desired needs of the users. The design has not been through the feasibility test includes strength and ability to withstand the load. To solve the problem, this study will use simulations that is performed using Finite Element Method (FEM) in SolidWorks. Having a researched and conducted a series of simulated observations using SolidWorks software, resulting that material used is good material and safe to be used for some part of the college chair. Keywords: Finite Element Method (FEM), simulation, chair